2020
DOI: 10.1039/d0cc03883k
|View full text |Cite
|
Sign up to set email alerts
|

The anticancer activity of an air-stable Pd(i)-NHC (NHC = N-heterocyclic carbene) dimer

Abstract: A new dinuclear Pd(I) complex coordinating two bis(NHC) ligands revealed an unsuspected stability despite the unsaturation of the two metal centres. Even more surprisingly, the compound showed a high and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…As shown in Table 1, the organometallic cages [Ag 4 (2) 2 ](OTf) 4 and [Au 4 (2) 2 ](OTf) 4 show considerable anticancer activity with the half maximal inhibitory concentration (IC 50 ) values ranging from 2.271 to 3.887 μM and 1.667 to 2.272 μM, respectively, which were similar or even more potent to those of cisplatin in some cancer cell lines (Supporting Information Table S3). [74][75][76] In addition, the relatively high IC 50 values of [Ag 4 (2) 2 ] (OTf) 4 and [Au 4 (2) 2 ](OTf) 4 toward L-02 cells indicate that they have relatively low toxicity to human normal hepatocyte cells (Table 1). To our knowledge, this represents the first example of TPE-based organometallic cages used for cell imaging and treatment of cancer cells.…”
Section: Mechanochromic Propertiesmentioning
confidence: 99%
“…As shown in Table 1, the organometallic cages [Ag 4 (2) 2 ](OTf) 4 and [Au 4 (2) 2 ](OTf) 4 show considerable anticancer activity with the half maximal inhibitory concentration (IC 50 ) values ranging from 2.271 to 3.887 μM and 1.667 to 2.272 μM, respectively, which were similar or even more potent to those of cisplatin in some cancer cell lines (Supporting Information Table S3). [74][75][76] In addition, the relatively high IC 50 values of [Ag 4 (2) 2 ] (OTf) 4 and [Au 4 (2) 2 ](OTf) 4 toward L-02 cells indicate that they have relatively low toxicity to human normal hepatocyte cells (Table 1). To our knowledge, this represents the first example of TPE-based organometallic cages used for cell imaging and treatment of cancer cells.…”
Section: Mechanochromic Propertiesmentioning
confidence: 99%
“…In this paper, we aimed to evaluate and compare the toxicity of two long and two short-chain PFASs toxicity in a physiological relevant and innovative liver mini-organs (organoids) at cellular level by measuring cell viability, structural histology and enzymatic activity. Organoids are 3D models that can recapitulate in vitro the physiology of organs and represent a platform in which it is possible to predict the effects of a compound more rapidly than in vivo [27][28][29][30][31]. Two long-chain (PFOS, PFOA) and two short-chain PFAS (HFBA: Heptafluorobutyric acid also known as perfluorobutyric acid; PFPA: Pentafluoropropionic anhydride) were tested.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently reported that organometallic Pd(0) derivatives containing purine-based N-heterocyclic carbenes exert significant antiproliferative activity against ovarian cancer cell lines, comparable to cisplatin even in resistant cell lines [ 211 ]. Moreover, following an evolution of Pd-based derivatives from the more common Pd(II) complexes to the Pd(0) ones, Scattolin and co-workers reported in 2020 about high and selective antiproliferative activity on different cancer cell lines and advanced preclinical ovarian cancer models of an original dinuclear Pd(I)-based complex, showing mechanisms of action different from that of cisplatin and mainly involving mitochondria [ 212 ]. These findings could pave the way towards the discovery of new alternatives among organopalladium derivatives endowed with antiproliferative action.…”
Section: Palladiummentioning
confidence: 99%